Governing the Commons in the Anthropocene: A Quantitative and Qualitative Assessment of Sasi Customary Law's Efficacy in Marine Conservation and Climate Resilience in the Maluku Islands - Grace Freya Purba; Farah Faiza; Evelyn Wang; Aaliyah El-Husaini; Benyamin Wongso; Sarah Armalia (Enigma in Law, 2025)
The escalating pressures of the Anthropocene, characterized by climate change and biodiversity loss, demand effective and equitable conservation paradigms. This study investigates Sasi, a form of customary marine tenure in the Maluku Islands, Indonesia, as a potential model for sustainable resource management and climate resilience. A mixed-methods, comparative longitudinal approach was employed across six coastal villages from 2015 to 2025. Three villages actively practicing Sasi were compared with three non-Sasi control villages. Quantitative data included underwater visual censuses for fish biomass, line-intercept transects for coral cover, and household surveys (n=300) to assess socio-economic conditions and climate resilience indicators. Qualitative data were gathered through semi-structured interviews with key stakeholders (n=60), focus group discussions (n=12), and participant observation to understand the governance mechanisms and community perceptions of Sasi. Sasi villages exhibited significantly higher mean fish biomass (4.5 ± 0.8 t/ha) compared to non-Sasi villages (1.9 ± 0.6 t/ha) (p<0.001). Live coral cover was more robust in Sasi sites, showing greater resistance to bleaching events. Socio-economically, Sasi communities reported higher, more stable fishing incomes and perceived greater food security. Qualitative analysis revealed that the efficacy of Sasi is driven by strong social cohesion, legitimate authority of the Kewang (customary guardians), and adaptive management informed by traditional ecological knowledge. In conclusion, the findings demonstrate that Sasi customary law is a highly effective institution for marine conservation, contributing significantly to ecological health and community climate resilience. The study underscores the critical importance of integrating customary governance systems into national and global conservation strategies to address the complex challenges of the Anthropocene.